HUBUNGAN ANTARA PANJANG TUNGKAI DAN POWER OTOT TUNGKAI DENGAN HASIL LARI 100 METER PADA SISWA KELAS VIII SMPN 1 PRAYA TENGAH TAHUN PELAJARAN 2016/2017 - Hairunnisha Hairunnisha; Mujriah Mujriah; Adi Suriatno (Universitas Pendidikan Mandalika, 2018)
The running speed of the sprint number is determined by the length of step and step frequency as stated by Jonath (1986: 58) that